2019
DOI: 10.3390/polym11122054
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Bubble Stretching Assisted Melt Extrusion for the Preparation of HDPE/UHMWPE/CF Composites

Abstract: In this work, a novel melt extrusion method under synergy of extensional deformation and in-situ bubble stretching (ISBS) and corresponding apparatus were reported. The structure and working principle were introduced in detail. Polymer composites composed of high density polyethylene (HDPE)/ultrahigh molecular weight polyethylene (UHMWPE)/carbon fiber (CF) were prepared by using this new method. Effects of CF and Azodicarbonamide (AC) contents on composites’ morphology, rheological, thermal, and mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…However, thermoplastic CFRP has some disadvantages, such as difficulties in resin impregnation, due to high melt viscosity and low resin flow, and mechanical properties due to weak bonding at the interface between the carbon fiber and polymer matrix over thermosetting CFRP [ 17 ]. Hence, extrusion and injection molding processes have been most frequently used to prepare thermoplastic CFRP using chopped carbon fibers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, thermoplastic CFRP has some disadvantages, such as difficulties in resin impregnation, due to high melt viscosity and low resin flow, and mechanical properties due to weak bonding at the interface between the carbon fiber and polymer matrix over thermosetting CFRP [ 17 ]. Hence, extrusion and injection molding processes have been most frequently used to prepare thermoplastic CFRP using chopped carbon fibers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There exist different flow fields in melt mixing device, including shear flow field and extensional flow field. It has been reported that the dispersion efficiency under the extensional flow is higher than that under the shear flow 19–21 when the deformation rate is equal. Moreover, although the introduction of HGBs into the polymer will reduce the dielectric constant of the composites slightly, 22–24 ball milling formed by HGBs is a well‐known effective way to break and disperse the fillers.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum blend ratio of UHMWPE used was 50%. In‐situ bubble stretching (ISBS) assisted extrusion 19 used a special vane extruder to produce 9% UHMWPE/HDPE/carbon fiber (CF) blend by introducing the synergy of extensional deformation and ISBS. An eccentric rotor extruder was employed to pretreat UHMWPE before compression molding 20 .…”
Section: Introductionmentioning
confidence: 99%